2015
DOI: 10.1080/07055900.2015.1045825
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Temperature and Precipitation Surface-Based and Reanalysis Datasets for the Canadian Arctic, 1950–2010

Abstract: The spatial and temporal consistency of seasonal air temperature and precipitation in eight widely used gridded observation-based climate datasets (CANGRD, CRU-TS3.1, CRUTEM4.1, GISTEMP, GPCC, GPCP, HadCRUT3, and UDEL) and eight reanalyses (20CR, CFSR, ERA-40, ERA-Interim, JRA25, MERRA, NARR, and NCEP2) was evaluated over the Canadian Arctic for the 1950-2010 period. The evaluation used the CANGRD dataset, which is based on homogenized temperature and adjusted precipitation from climate stations, as a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 65 publications
8
62
0
Order By: Relevance
“…All reanalyses displayed an overall warm bias in agreement with previous studies (e.g. Rapaić et al 2015) with a median bias of +3.4 °C for REM. Contrary to reanalyses, RCMs had a cold bias in TNn with MEM bias of approximately −2.8 °C.…”
Section: Biasessupporting
confidence: 77%
See 2 more Smart Citations
“…All reanalyses displayed an overall warm bias in agreement with previous studies (e.g. Rapaić et al 2015) with a median bias of +3.4 °C for REM. Contrary to reanalyses, RCMs had a cold bias in TNn with MEM bias of approximately −2.8 °C.…”
Section: Biasessupporting
confidence: 77%
“…Trace precipitation amounts for solid precipitation were assigned values from 0.03 to 0.07 mm that varied inversely with latitude following Mekis and Vincent (2011). CFSR, MERRA and ERA-Interim monthly mean temperature and precipitation data were previously evaluated over the Canadian Arctic by Rapaić et al (2015) and over the entire Arctic by Lindsay et al (2014). Both papers indicate that MERRA and ERA-Interim have relatively small warm and wet biases compared to other reanalyses, while CFSR was found to have particularly large positive precipitation biases.…”
Section: Atmospheric Reanalyses and Gridded Surface Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of documented differences in gridded temperature datasets over Canada (Rapaic et al, 2015), surface temperature trends were derived from a blend of six reanalysis products: the European Centre for Mid-Range Weather Forecasting…”
Section: Surface Temperaturementioning
confidence: 99%
“…4); however, the change point analysis showed an important decrease in the year 1972 from 369 to 321 mm yr −1 for the mean annual precipitation (Table 3). Vincent et al (2015) investigated long-term trends in precipitation records over Canada for the period between 1948 and 2012 using the gridded and spatially interpolated CANGRD dataset (Rapaic et al, 2015). For the region around Havikpak Creek Vincent et al (2015) showed significant spatial variability with a small increase of less than 10 % in annual precipitation.…”
Section: Changing Climatementioning
confidence: 99%